Upregulation of P2X3 receptors in primary afferent pathways involves in colon-to-bladder cross-sensitization in rats - Dong, XingYou; Yang, Yang; Luo, Shengjun; Deng, Xiaohong; Tang, Wei (Frontiers in Physiology, 2022)
Background: Clinical investigation indicates a high level of co-morbidity between bladder overactivity and irritable bowel syndrome. The cross-sensitization of afferent pathways has been demonstrated to be the main reason for the cross-organ sensitization, but the underlying mechanism is unclear. Methods: A single dose of 2, 4, 6-trinitrobenzene sulfonic acid (TNBS) was applied to induce the colitis rat models by intracolonic administration. All rats were randomly divided into three groups: control, TNBS-3-day, and TNBS-7-day groups. Western blot and immunofluorescent staining were performed to detect the expression of the P2X3 receptor. The spontaneous contractions of the detrusor strip were measured to evaluate the detrusor contractility function. The micturition function was measured by a cystometry experiment. The intercontractile interval (ICI) and maximum bladder pressure (BP) were recorded. Results: The distal colon from colitis showed serious tissue damage or chronic inflammation after TNBS instillation (p < 0.01). However, there were no detectable histological changes in bladder among groups (p > 0.05). TNBS-induced colitis significantly increased P2X3 receptor expression on the myenteric and submucosal plexus of the distal colon and urothelium of the bladder, especially at day 3 post-TNBS (p < 0.05). Meanwhile, the expression of the P2X3 receptor on DRG neurons was increased in TNBS-induced colitis (p < 0.01). The detrusor strip of rats exhibited detrusor overactivity after days 3 and 7 of TNBS administration (p < 0.01), but inhibition of the P2X3 receptor had no effect (p > 0.05). Moreover, the rats with colitis exhibited the micturition pattern of bladder overactivity, manifested by decreased ICI and increased maximum BP (p < 0.05). Interestingly, inhibition of the P2X3 receptor by intrathecal injection of A-317491 alleviated bladder overactivity evoked by TNBS-induced colitis (p < 0.05). Conclusion: The upregulation of the P2X3 receptor in an afferent pathway involved in bladder overactivity evoked by TNBS-induced colonic inflammation, suggesting that the P2X3 receptor antagonist may be an available and novel strategy for the control of bladder overactivity.